Sputtered ZnO Rods/Film Structure on Different Substrates - Van Tri Le; Phan Tan Sang Ho; Bao Quan Tran; Hoang Trung Huynh; Hai Dang Ngo; Thi Kim Hang Pham (Journal of Technical Education Science, 2024)
The wide investigation of zinc oxide (ZnO) nanorods is primarily driven by their exceptional utility in several industries, such as solar cells, sensors, photodetectors, photocatalysts, microchip technology, and piezoelectric transducers. There has been a growing focus in environmental defense applications on the use of ZnO nanorods as photocatalysts. This investigation discusses the growth of ZnO rods on ZnO films using the radio-frequency magnetron sputtering method at a temperature of 400 °C. The growth was performed on several substrates including Si (100), Si (111), and SiO2 substrates. A careful examination was conducted to examine the influence of the substrate on the structure and surface morphology of ZnO rods/film. Based on the X-ray diffraction patterns, it was seen that both the films and rods exhibited a high degree of crystallinity and exhibited a wurtzite structure. Furthermore, there was a preferred orientation along the (002) direction, which was perpendicular to the substrate. Scanning electron microscopy images demonstrated the significant effect of substrates on both the thickness of ZnO films and the length of rods. The findings indicated that these structures were well-suited for several applications, including thermionic/field emission, solar cells, UV detectors, and gas sensors.